Asymptomatic Bacteriuria in Kisangani Gestational Women: Prevalence and Germs Involved - Mwetaminwa Sangani Georgette; Katenga Bosunga Gédéon; Bosenge-Nguma Jean-Didier; Labama Otuli Noël; Maindo Alongo Mike-Antoine; Juakali Sihalikyolo Jean-Jeannot; Komanda Likwekwe Emmanuel; Modia O’yandjo Antoine (Archives of Current Research International, 2022)
Introduction: Urinary tract infection is a real public health problem. Asymptomatic bacteriuria, when not detected and treated, turns into pyelonephritis in 30 to 40% of cases, leading to both maternal and fetal complications, which would explain its high morbidity during pregnancy, especially in developing countries. Our objective is to determine the prevalence of asymptomatic bacteriuria and to identify the germs involved in Kisangani. Methods: This is a descriptive, prospective, multi-site study conducted among 424 pregnant women in four health facilities in the city of Kisangani, all aged 14 to 45 years, received and followed in prenatal consultations from November 25, 2019 to June 25, 2020 and having given written informed consent to participate in the study. Cytobacteriological examination of urine was performed after collection of mid-morning urine in the laboratory of the University Clinics of Kisangani. The data collected were compiled using the Excel spreadsheet program (Microsoft, CDC, 2010) and then imported for analysis using the Epi Info software© 7.2.2.6 in its Stat Cal function. Results: The prevalence of asymptomatic bacteriuria was 45.75%. Pregnant women between 20 and 34 years old had the most asymptomatic bacteriuria with 72.68%, pauci pares in 48.97% and in their second trimester of pregnancy in 61.34% of cases. 86.08% lived in a union, 60.82% were unemployed, 65.98% had secondary education, 50% had a low socioeconomic level and 48.97% had a history of cervico-vaginal infection. Escherichia coli and Staphylococcus aureus were the most frequently encountered germs. Conclusion: Asymptomatic bacteriuria is a reality among pregnant women in Kisangani. Escherichia coli and Staphylococcus aureus are the most frequently encountered germs; screening and management on the basis of culture and antibiogram results are essential for maternal-fetal well-being.